THIAMINE IN FISH AND ITS DEGRADATION DURING THERMAL PROCESSING OF SALTED-BOILED FISH - Suparno Suparno; S.W. Hanson; A.J. Rosenthal (Indonesian Fisheries Research Journal, 1996)
The existence of different forms of thiamine in the llesh of rainbow trout (Salmo gairdneri) and  their losses during thermal processing have been investigated.